P3.291 Associations of Chlamydia Trachomatis Infection in Men and Women with Genital Discharge Syndromes in Johannesburg, South Africa. (13th July 2013) - Radebe, F; Ricketts, C; Kekana, V; Vezi, A; Basson, I; Magooa, P; Bhojraj-Sewpershad, N; Gita, G de; Maseko, V; Lewis, D A
Abstract : Background: As part of an on-going STI microbiological surveillance programme, we investigated associations between Chlamydia trachomatis infection and the demographic, clinical, microbiological and behavioural characteristics of patients presenting with either male urethral discharge syndrome (MUDS) or vaginal discharge syndrome (VDS) to a public healthcare facility in Johannesburg, South Africa Methods: 1, 218 MUDS and 1, 232 VDS cases were consecutively recruited during 6 annual surveys, starting in 2007. Genital discharge pathogens were detected using a molecular assay for N. gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma genitalium and by microscopy of vaginal smears (bacterial vaginosis, Candida ). Serology was used to detect syphilis, HSV-2 and HIV infections. Chi-squared tests and logistic regression analyses were used to identify predictors of C. trachomatis infection. Results: Overall, 286 (23.5%) men and 197 (16.0%) women were C. trachomatis positive, with the highest prevalence observed in men (30.5%) and women (25.9%) aged 20–24 years. In the multivariate analysis, C. trachomatis was less likely to be detected in MUDS patients co-infected with N. gonorrhoeae (aOR 0.36, 95% CI, 0.26–0.49) and HSV-2 (aOR 0.70, 95% CI, 0.51–0.95) as well as patients who had received antibiotics recently (aOR 0.43. 95% CI, 0.20–0.91). In contrast, the likelihood of C. trachomatis infection was higher in VDS patients co-infected with either N. gonorrhoeae (aOR 2.22, 95% CI, 1.48–3.32) or M. genitalium (aOR 2.24, 95% CI, 1.45–3.47) infection but lower in women who were older (aOR 0.68, 95% CI 0.60–0.77) or who had Candida morphotypes detected (aOR 0.66, 95% CI 0.44–0.98). Conclusion: The increased likelihood of co-existent gonococcal or M. genitalium infections, but the decreased likelihood of Candida infection, in women with VDS-associated chlamydial infection suggests that these women are at higher risk of STIs, and potentially HIV. Paradoxically, gonococcal infection as well as recent antibiotic use, reduced the likelihood of MUDS patients having chlamydial infection.